Perlindungan Hukum Bagi Direksi Yang Diberhentikan Melalui Keputusan Sirkuler Yang Tidak Sah: Studi Perbandingan Indonesia, Singapura, Britania Raya, dan Australia - Ferencia, Viony; Azwar, Tengku Keizerina Devi; Windha (PT Matra Cendikia Abadi, 2025)
Circular resolution is one of the decision-making mechanisms by shareholders other than the GMS has become one of the mechanisms often used by shareholders to make decisions in limited companies. However, the use of circular resolutions is inseparable from potential juridical problems, among others related to abuse of authority, especially in the context of dismissal of members of the board of directors. This article aims to examine the utilization of circular resolutions in the limited liability company system in Indonesia, both in terms of normative application and risk implications. In addition, this research also compares the legal systems in Singapore, the United Kingdom, and Australia in order to obtain a more comprehensive perspective on the regulation of the circular resolution mechanism. The method used is normative law. The nature of the research is prescriptive using secondary data obtained through data collection and data analysis techniques. The research approach uses a statutory approach, case approach, and comparative approach. The results show that legal protection for directors who are dismissed through circular decisions is not yet optimal. This is due to the regulation regarding circular decisions in Indonesia which is currently limited to only 1 (one) article, and there is no further regulation regarding procedures, time periods, and no restrictions on the use of circular decisions, so that it has the potential to cause legal uncertainty and less than optimal legal protection for PT directors in Indonesia. Therefore, to ensure legal certainty and optimal legal protection for directors, it is necessary to have bright and clear arrangements related to circular decisions that present progressive positive law in mitigating the risk of misuse of circular decisions in Indonesia.